Efficient water electrolysis hydrogen production catalyst material, coating, preparation method and application of efficient water electrolysis hydrogen production catalyst material

The modified transition metal catalyst coating is prepared through thermal spraying technology, which solves the problem of low current density of traditional Rainey nickel catalyst coating, and achieves significant improvement in electrode current density and controllability. It is suitable for large-scale hydrogen production systems.

CN119710790APending Publication Date: 2025-03-28ANHUI MA STEEL SURFACE TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411830457.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The current density of the traditional Rainey nickel catalyst coated electrode is low, resulting in large-scale hydrogen production systems having problems such as large-scale and poor operating stability.

Method used

A modified transition metal catalyst coating is prepared using thermal spraying technology. The specific steps include mixing and ball milling of Ni, Cu, Mo, Cr, polyphenyl, BN powders, adding dispersant and binder, granulating and heat treatment, and finally forming the coating through an atmospheric plasma spraying process.

Benefits of technology

It significantly improves the current density of the electrode, does not contain precious metals, has controllable cost and good durability, and is suitable for the needs of large-standard hydrogen production systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710790A_ABST
    Figure CN119710790A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of surfaces, in particular to an efficient water electrolysis hydrogen production catalyst material, a coating, a preparation method and application of the efficient water electrolysis hydrogen production catalyst material, the coating, the preparation method and the application of the efficient water electrolysis hydrogen production catalyst material. The invention further provides a preparation method of the Ni, Cu, Mo, Cr, polybenzoate and boron nitride composite powder and a method for preparing a high-efficiency catalyst coating from the composite powder. Compared with traditional Raney nickel, the high-efficiency catalyst coating prepared by the method has the advantages that the current density is greatly improved, and the high-efficiency catalyst coating does not contain precious metal, is controllable in cost, and is relatively good in durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of surface technology, and in particular to a high-efficiency water electrolysis hydrogen production catalyst material and coating, a preparation method and application thereof. Background Art

[0002] Due to its simple electrolyzer structure and low cost, alkaline water electrolysis (ALK) technology is currently the most mature and most commercially used water electrolysis hydrogen production technology in my country.

[0003] The electrolyzer is the core component of the alkaline water electrolysis hydrogen production system, and the electrode is one of the key components that determine the performance of the electrolyzer. The shape and structure of the electrode itself and the catalyst coating covering the electrode surface are the most critical factors determining the efficiency of hydrogen production in the electrolyzer. There are many catalyst material systems that can be used for water electrolysis catalysis: (1) platinum group metal catalysts, including catalysts of elements such as platinum, palladium, rhodium, ruthenium, and iridium. Although the above catalysts have high catalytic efficiency and strong stability, they are extremely expensive; (2) hydroxide catalysts, including nano-ferrites, metal oxides, copper oxides, etc. The catalytic efficiency and stability of the above catalysts are greatly affected by the outside world; (3) metal compound catalysts, such as molybdenum sulfide catalysts, etc. These catalysts have poor stability; (4) transition metal catalysts, including nickel, iron, cobalt, copper, molybdenum, etc. The above catalysts have high catalytic efficiency, good stability, and moderate prices, and are currently widely used.

[0004] In the alkaline water electrolysis hydrogen production system, the electrode is one of the key factors that determine the current density of the electrolyzer. In the past, the electrodes of the alkaline water electrolysis hydrogen production electrolyzer usually used a nickel electrode mesh with a deposited Raney nickel catalyst coating. The catalytic activity of the Raney nickel catalyst is general, so the current density of the electrolyzer is generally low when working. With the rapid development of the hydrogen production industry in recent years, the demand for green hydrogen has increased, so the demand for large-scale electrolyzers has also gradually increased. At present, large-scale electrolyzers are often simply enlarged by increasing the size of the electrolyzer and the electrode or increasing the number of stacks, resulting in large-scale hydrogen production systems. Problems such as large size and low operating stability. Therefore, increasing the current density of the electrode is one of the feasible ways to solve the above problems, and it is also the mainstream trend of future electrolyzers. This view is now gradually accepted by most companies.

[0005] At present, the main preparation methods of catalyst coatings include thermal spraying, brushing / rolling and electroplating / chemical plating. Among them, thermal spraying technology has the advantages of a wide range of sprayable materials, uniform coating, and high bonding strength, but it also has the disadvantage of low raw material utilization rate. Therefore, thermal spraying is a more ideal preparation method for non-precious metal catalyst coatings.

[0006] In view of this, the present invention adopts thermal spraying technology to prepare a modified transition metal catalyst coating to solve the problem of low current density of the traditional Raney nickel catalyst coating electrode. Summary of the invention

[0007] The purpose of the present invention is to solve the problem of low current density of traditional Raney nickel catalyst coating electrodes, and to provide a high-efficiency water electrolysis hydrogen production catalyst material and coating, a preparation method and application thereof. Specifically, by designing and preparing a high-efficiency catalyst material and a corresponding coating, the current density of the electrode is greatly improved, and the electrode has the characteristics of being free of precious metals, cost-controllable, and having good durability.

[0008] In order to achieve the above object, the present invention discloses a method for preparing a high-efficiency water electrolysis hydrogen production catalyst material, comprising the following steps:

[0009] S1, Ni, Cu, Mo, Cr, polyphenylene ester and BN are mixed, water and ethanol are added, stirred evenly and then ball milled. The purpose of ball milling is to make each component evenly distributed, so as to obtain a catalyst coating with stable performance;

[0010] S2, after adding the dispersant, continue ball milling to fully disperse the components;

[0011] S3, after adding the binder, continue ball milling to improve the cohesion of the agglomerated powder;

[0012] S4, spray granulation to obtain agglomerated powder. The spray granulation process causes the powder monodisperse particles with smaller particle sizes to agglomerated powder particles with larger sizes, thereby improving the powder fluidity. Subsequently, the agglomerated powder size is sieved to match the subsequent thermal spraying process;

[0013] S5, heat-treating the agglomerated powder after granulation in step S4 to remove binder. The heat treatment after granulation mainly serves to remove polyacrylic acid and polyvinyl alcohol from the agglomerated powder to reduce their influence on spraying.

[0014] In the step S1, the mass ratio of Ni, Cu, Mo, Cr, polyphenyl ester and BN is 50-100:0-50:10-20:5-30:20-50:0-10, and the ball milling time is 5-8 hours; wherein the particle size of Ni, Cu, Mo, Cr, polyphenyl ester and BN powder is less than 30 μm.

[0015] In the step S2, the dispersant is polyacrylic acid, and the ball milling time is 1 to 2 hours; the purpose of adding polyacrylic acid is to evenly disperse the powders in the solution.

[0016] In step S3, the binder is polyvinyl alcohol, and the ball milling time is 1 to 2 hours; the purpose of adding polyvinyl alcohol is to increase the cohesive force between the agglomerated particles and improve the fluidity of the granulated powder.

[0017] In the step S4, after granulation, agglomerated powders with a particle size range of 15-45 μm are screened out.

[0018] In step S5, the specific process of heat treatment for debinding is as follows: slowly heating the agglomerated powder to 300-400°C, keeping the temperature for 1-2 hours, and cooling to room temperature with the furnace; the heat treatment after granulation mainly serves to discharge polyacrylic acid and polyvinyl alcohol from the agglomerated powder to reduce their influence on spraying.

[0019] The invention also discloses a high-efficiency water electrolysis hydrogen production catalyst material prepared by the preparation method.

[0020] The present invention also discloses a method for preparing a high-efficiency water electrolysis hydrogen production catalyst coating, wherein the high-efficiency water electrolysis hydrogen production catalyst material is deposited onto an electrode surface by an atmospheric plasma spraying process to form a coating, wherein the thickness of the coating is >50 μm.

[0021] The invention also discloses a high-efficiency water electrolysis hydrogen production catalyst coating prepared by the preparation method and application of the high-efficiency water electrolysis hydrogen production catalyst coating in an alkaline water electrolysis hydrogen production electrolyzer.

[0022] Compared with the prior art, the beneficial effects of the present invention are:

[0023] 1. The present invention uses Ni as the main phase, adds Cu to reduce the cost, adds Mo to improve the catalytic activity, and adds Cr to improve the stability. Polyphenyl ester and boron nitride are used as pore-forming aids during spraying, and oxidation during the spraying process is reduced, thereby obtaining a NiCuMoCr multi-component catalyst with excellent performance and good durability;

[0024] 2. The transition metal component NiCuMoCr in the high-efficiency catalyst material of the present invention is a catalytic component and the main catalytic component of the coating after spraying. The above-mentioned catalytic components and their proportions are the results obtained by the inventors after careful screening and optimization through a large number of experiments in a long-term practice process. Polyphenyl ester and BN are spraying aids, which are mainly used to form relatively uniform pores in the entire coating during the spraying process, while reducing the oxidation of the catalytic components during the spraying process, thereby increasing the specific surface area of ​​the catalytic components and making them have a higher catalytic efficiency. The addition of the Cr component reduces the possibility of deactivation of the catalytic components during the catalytic process, thereby improving the durability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the metallographic structure of the NiCuMoCr catalyst coating;

[0026] Figure 2 The linear voltammetric scan results of the catalyst coating in Example 1;

[0027] Figure 3 The linear voltammetric scan results of the catalyst coating in Example 2;

[0028] Figure 4 The linear voltammetric scanning result of the catalyst coating in Comparative Example 1;

[0029] Figure 5 The linear voltammetric scanning result of the catalyst coating in Comparative Example 2;

[0030] Figure 6 Comparison results of catalyst coating durability test. DETAILED DESCRIPTION

[0031] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.

[0032] Example 1

[0033] (1) Ni, Cu, Mo, Cr, polyphenylene ester, and BN original powders with a particle size of 1 to 30 μm were weighed in a ratio of 90:10:15:10:35:5, mixed evenly with a 20% ethanol aqueous solution in a ratio of 30:50, and then placed in a planetary ball mill for 8 h;

[0034] (2) adding 10% polyacrylic acid aqueous solution to the above slurry and continuing ball milling for 2 hours;

[0035] (3) Add 10% polyvinyl alcohol aqueous solution to the above slurry and continue ball milling for 2 hours;

[0036] (4) After filtering out the ball-milled slurry, granulation is performed using a granulation device, and after granulation, agglomerated powder with a particle size range of 15-45 μm is screened out;

[0037] (5) slowly heating the agglomerated powder to 400°C at a rate of 10°C, keeping the temperature for 2 hours, and then cooling it to room temperature in the furnace before taking it out for later use;

[0038] (6) After the nickel electrode mesh is degreased and sanded, the above powder is sprayed onto the surface of the nickel electrode mesh using atmospheric plasma spraying technology. The atmospheric plasma spraying process parameters are shown in Table 1. The coating thickness is about 70 μm. Figure 1 shown.

[0039] Table 1 Atmospheric plasma spraying process parameters

[0040]

[0041] Example 2

[0042] The original powder ratio of Ni, Cu, Mo, Cr, polyphenylene ester and BN was changed to 50:50:15:10:35:5, and the rest was the same as in Example 1.

[0043] Comparative Example 1

[0044] (1) After the nickel electrode mesh is degreased and sanded, commercially available NiAl alloy powder is sprayed onto the surface of the nickel electrode mesh using atmospheric plasma spraying technology. The atmospheric plasma spraying process parameters are shown in Table 1, and the coating thickness is about 70 μm;

[0045] (2) The nickel mesh is immersed in a 30 wt % NaOH solution for activation for 7 days, and then washed with deionized water and dried to obtain a nickel mesh.

[0046] Comparative Example 2

[0047] (1) After the nickel electrode mesh is degreased and sanded, commercially available NiAlMo alloy powder is sprayed onto the surface of the nickel electrode mesh using atmospheric plasma spraying technology. The atmospheric plasma spraying process parameters are shown in Table 1, and the coating thickness is about 70 μm;

[0048] (2) The nickel mesh is immersed in a 30 wt % NaOH solution for activation for 7 days, and then washed with deionized water and dried to obtain a nickel mesh.

[0049] Comparative Example 3

[0050] The original powder ratio of Ni, Cu, Mo, Cr, polyphenylene ester and BN was changed to 90:10:15:0:35:5, and the rest was the same as in Example 1.

[0051] Comparative Example 4

[0052] The original powders of Ni, Fe, Mo, Cr, polyphenylene ester and BN were weighed in a ratio of 90:10:15:10:35:5, and the rest were the same as in Example 1.

[0053] The nickel electrode meshes obtained in Example 1, Example 2 and Comparative Examples 1, Comparative Example 2 and Comparative Example 4 (the same nickel electrode meshes were used for the cathode and anode, the same below) were subjected to linear voltammetric scanning at 1.2 to 2.2 V (VSRef) and -1.2 to -2.2 V (VSRef) (5 scans each) using an electrochemical workstation under the same conditions (80°C, 30 wt% KOH solution). The results are shown in the attached figure. Figures 2 to 6As shown. The results show that the overpotential of Example 1 is more than 100mV lower than that of Comparative Example 1. At the same time, at a voltage of 2.0V, the current density of Example 1 is about 3 times that of Comparative Example 1, indicating that the current density of Example 1 has been significantly improved by adjusting the composition compared with the conventional Comparative Example 1; Mo doping (Comparative Example 2) significantly improves the current density of binary Raney nickel (Comparative Example 1), but compared with Comparative Example 2, the current density of Example 1 at a voltage of 2.0V is further increased by more than 20%, indicating that the current density of the NiCuMoCr system of the present invention is also significantly improved relative to the current density of Mo-doped Raney nickel (Comparative Example 2); the current density of Example 2 at 2.0V is better than that of Comparative Example 1 (increased by about 76%), and slightly worse than that of Comparative Example 2 (the difference is within 5%), but because a high proportion of Cu is used, it has a more obvious advantage in terms of cost.

[0054] The durability test of 10 φ200 mm nickel electrode meshes prepared under the conditions of Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 was carried out in a test tank (the test current density of Example 1 was 6000 A / m 2 , the test current density of comparative example 1 is 4000A / m 2 , the test current density of comparative example 2 is 6000A / m 2 , the test current density of comparative example 3 is 6000A / m 2 ), the results are shown in the attached Figure 6 The results show that after 7 days of durability testing, Example 1 has a 2 The cell pressure hardly changes at a current density of 4000A / m, indicating that the catalyst coating has good durability; while the cell pressure of Comparative Example 1 does not change at a current density of 4000A / m 2 After 7 days of durability testing at a current density lower than that of Example 1, the cell voltage increased significantly (0.1 V) and exceeded that of Example 1, indicating that the durability of the catalyst coating was poor. 2 After 7 days of durability test at a current density of 6000A / m (same as Example 1), the cell voltage also increased (0.04V), indicating that although the introduction of Mo in the catalyst coating can increase the current density, it will affect the durability of the catalyst coating; Comparative Example 3 at 6000A / m 2 After 7 days of durability testing at a current density of 1.5 A / m (same as Example 1), the voltage also increased (0.06 V), indicating that the introduction of Cr can indeed improve the durability of the catalyst coating; Comparative Example 4 at 6000 A / m 2The test was carried out at a current density of 1.547 W (the same as that in Example 1). After only 4 days of testing, the voltage rose by about 1.1 V and the voltage had a tendency to continue to rise. At this time, the test voltage had reached 2.08 V. After comprehensive consideration, the test was stopped. Fe is another element used to reduce costs and replace Ni. It is usually used for wet preparation of catalyst coatings. Since the Fe-containing catalyst coating is prone to chemical reaction with the aqueous solution during powder preparation, spraying and service, the catalytic efficiency of the catalyst coating is reduced. Therefore, the voltage rises very quickly during the service process, that is, the durability of the coating is very poor.

[0055] In summary, the high-efficiency catalyst coating of the present invention has significantly improved current density compared to conventional Raney nickel catalyst coatings. The added components such as Cr and BN are beneficial to improving the durability of the catalyst coating. The added Cu can also play a beneficial effect in cost control, which is conducive to the commercialization of the high-efficiency catalyst coating of the present invention.

[0056] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.

Claims

1. A method for preparing a highly efficient catalyst material for hydrogen production by water electrolysis, characterized in that: The following steps are involved: S1, Ni, Cu, Mo, Cr, polyphenylene ester and BN are mixed, water and ethanol are added, stirred evenly and then ball milled; S2, after adding the dispersant, continue ball milling to fully disperse the components; S3, after adding the binder, continue ball milling to improve the cohesion of the agglomerated powder; S4, spray granulation followed by sieving to obtain agglomerated powder; S5, heat-treating the agglomerated powder after granulation in step S4 to remove binder.

2. The method for preparing a high-efficiency water electrolysis hydrogen production catalyst material according to claim 1, characterized in that: In the step S1, the mass ratio of Ni, Cu, Mo, Cr, polyphenyl ester and BN is 50-100:0-50:10-20:5-30:20-50:0-10, the ball milling time is 5-8 hours, and the particle size of Ni, Cu, Mo, Cr, polyphenyl ester and BN powder is less than 30 μm.

3. The method for preparing a high-efficiency water electrolysis hydrogen production catalyst material according to claim 1, characterized in that: In the step S2, the dispersant is polyacrylic acid, and the ball milling time is 1 to 2 hours.

4. The method for preparing a high-efficiency water electrolysis hydrogen production catalyst material according to claim 1, characterized in that: In the step S3, the binder is polyvinyl alcohol, and the ball milling time is 1 to 2 hours.

5. The method for preparing a high-efficiency water electrolysis hydrogen production catalyst material according to claim 1, characterized in that: In the step S4, after granulation, agglomerated powders with a particle size range of 15-45 μm are screened out.

6. The method for preparing a high-efficiency water electrolysis hydrogen production catalyst material according to claim 1, characterized in that: In step S5, the specific process of heat treatment for debinding is as follows: slowly heating the agglomerated powder to 300-400° C., keeping the temperature for 1-2 hours, and cooling to room temperature along with the furnace.

7. A high-efficiency catalyst material for hydrogen production by electrolysis of water prepared by the preparation method according to any one of claims 1 to 6.

8. A method for preparing a high-efficiency catalyst coating for hydrogen production by water electrolysis, characterized in that: The high-efficiency water electrolysis hydrogen production catalyst material described in claim 7 is deposited onto the electrode surface through an atmospheric plasma spraying process to form a coating, and the thickness of the coating is >50 μm.

9. A high-efficiency water electrolysis hydrogen production catalyst coating prepared by the preparation method as claimed in claim 8.

10. Use of the high-efficiency water electrolysis hydrogen production catalyst coating as claimed in claim 9 in an alkaline water electrolysis hydrogen production electrolyzer.

Citation Information

Cited By

  • Low-overpotential high-activity catalyst coating for hydrogen production by electrolysis of water, preparation method and application of low-overpotential high-activity catalyst coating

    CN121250426A